2010
DOI: 10.1039/b915008k
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species activity and chemical speciation of size-fractionated atmospheric particulate matter from Lahore, Pakistan: an important role for transition metals

Abstract: In this study a sensitive macrophage-based in vitro reactive oxygen species (ROS) assay was coupled with chemical fractionation tools and a year-long sampling program to further our understanding of the role of water-soluble metals in aerosol toxicity. The location is the polluted urban environment of Lahore, Pakistan, where we collected 24 h PM10 and PM2.5 samples every 6(th) day from January 2007 through January 2008. The intrinsic (i.e. particulate matter (PM) mass-normalized) toxicity of the Lahore aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 86 publications
5
90
0
1
Order By: Relevance
“…Particles especially PM widely exist in the environment and may carry ROS within gas phase [13] or water phase (aerosol) [34] into the lower respiratory tract to create an increased risk on health. There is growing evidence for oxidative stress in response to air pollution in different organs [35].…”
Section: Discussionmentioning
confidence: 99%
“…Particles especially PM widely exist in the environment and may carry ROS within gas phase [13] or water phase (aerosol) [34] into the lower respiratory tract to create an increased risk on health. There is growing evidence for oxidative stress in response to air pollution in different organs [35].…”
Section: Discussionmentioning
confidence: 99%
“…These correlation analyses draw upon prior measurements reported elsewhere Shafer et al, 2010) and new measurements made in this study. Statistical analyses were limited to 13 monthly-average benzyl sulfate measurements, and other data with higher time resolution were averaged accordingly.…”
Section: Potential Sources Of Benzyl Sulfatementioning
confidence: 99%
“…Recent studies suggest that the role of coarse PM on asthma and other diseases has been significantly underestimated (Becker et al, 2005;Becker and Soukup, 2003). Some other studies also demonstrated that Cu in coarse PM was strongly associated with the redox activity of these particles Shafer et al, 2010). This manuscript describes the development of a technique for online measurement of Cu in ambient coarse PM.…”
Section: Introductionmentioning
confidence: 94%